Analisis Penerapan Green Supply Chain Management Pada Kemasan Ibc Di PT. DC Cilegon - Firdaus, Ridho; Gandara, Ganjar Sidik; Pratama, Hendra (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2023)
Intermediate Bulk Container (IBC) is a type of tank used in packaging, shipping & storage efficiently and safely applied to various types of chemical industries made from liquid. However, with a high number of uses and the price of this IBC tank is relatively expensive creating new high cost for industry. IBC with strong and durable material characteristics, has potential to improve its usage. To gain efficiency and positive effects on the environment, the concept of Reduce, Reuse, and Recycle (3R) is the method used by PT DC Cilegon. The purpose of this study is to analyze the reuse of IBC tanks so that the level of efficiency can be expressed in numbers. The data used is the use of IBC in Delivery Note letters for the period of September 2022 to January 2023. The result are 284 IBC was delivered and reused with a ratio of 2.39 times per IBC. Its mean that PT DC Cilegon was increasing efficiency of IBC usage 23,67%. This is the application of the concept of green industry (Green Manufacturing) with focus on Green Supply Chain which has positive impact for environment. Keywords: IBC, Reduce Reuse Recycle (3R), Efficiency, Green Manufacturing, Green Supply Chain.